Demography and Outcome of Pediatric Traumatic Brain Injury; Experience from a University Teaching Hospital in Nepal - Dahal, Sandesh; Shrestha, Dipendra K; Pradhanang, Amit B; Sedain, Gopal; Shilpakar, Sushil K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2022)
Introduction Traumatic brain injury (TBI) is one of the significant causes of disability and death. It is a common cause of emergency neurosurgical consultation. Due to differences in physiology and management strategy, outcomes of pediatric TBI are different. This study purposes to describe the demography, clinical-radiological characteristics, and outcome of patients with pediatric TBI. Methods A retrospective study of 112 children of age up to 18 years admitted to the Neurosurgical Department in Tribhuvan University Teaching Hospital (TUTH) following TBI from August 2021 to July 2022 was conducted. Variables analyzed were the demographics, clinical characteristics, imaging findings, management strategies, and outcome. Results Median age was 5.5 years. The male-to-female ratio was 2.3:1. Falls followed by road accidents were the most common mode of injury. A significant number of patients [62(55.3%)] presented after 24 hours of injury. Vomiting [67(59.8)] was the commonest symptom followed by loss of consciousness [60(53.6%)]. Post-traumatic seizure was observed in 13(11.6%) of the children; however, had no association with the outcome. Mild, moderate, and severe TBI were seen in 80.3%, 17.8%, and 1.7% respectively. Extra-axial hematomas (40%) were the most common findings followed by skull fractures (33.9%). ICU was required in [13(11.6%)] and [34(30%)] required surgery. Craniotomy (30.3%) was the most common procedure. Good outcome at discharge was seen in [107(95.5%)] of patients. Conclusion Pediatric TBI is a common cause of neurosurgical consultation. Falls and RTAs are the commonest causes in our cohort. In our study, a significant number of the patients presented after 24 hours of injury, and most of the children had good outcomes at discharge.